German federalism, its basic features and constitutional principles - Al-Najjar, Sherzad Ahmed; Majed, Dlawar Othman (Journal of Legal and Political Studies, 2019)
The issue of federalism is one of the most captivating issues for study at present، but what has been written and discussed about federalism is only a small section of the excessive legacy of the experience of countries that have taken federalism as a state. This research aims to demonstrate the effect of the federal state on the working nature of the German constitutional institutions، by explaining the historical stages of German Federal configuration as well as defining the working areas of the German state's constitutional institutions and their powers، which resulted in the general acceptance of the values and the required measures to implement the federal system with identifying the most important basic principles of the governance system according to the basic law، particularly the principle of federalism and human dignity.
Keywords: Germany; Federalism; Constitution; Federal State; Constitutional Institutions; Federal System; Human Dignity